Enhancing and Enlarging the Pool of Black Teachers. Final Report of the FIPSE Project - Brown, William C.; Southern Regional Education Board, Atlanta, GA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This project was designed to enhance and enlarge the pool of black teachers and to demonstrate the extent to which this intervention model could be effective in achieving this goal. The major activities of the project consisted of a series of faculty development workshops designed to hone faculty skills in test item analysis and construction, and curriculum and instruction improvement; and in the development of a comprehensive 5-year plan to guide efforts to strengthen the undergraduate education of education majors. Since the implementation of all components of the project was completed in December, 1990, the full impact of the project cannot be definitely measured at this time. Nevertheless, some positive outcomes are recognizable. For instance, limited quantitative data show an increase of 5 to 9 percent in the number of students applying for admission to teacher education in the participating institutions, as well as similar increases in the number of students admitted, enrolled, graduated, and certified to teach. Additionally, some of the improvements made in the areas of curriculum and instruction have been institutionalized, and some of the materials developed would, no doubt, be useful to interested institutions. It is significant to note also that this model of intervention is easily replicated. Seven appendixes provide outlines for program and curriculum development and the strategic plan of Dillard University (New Orleans, Louisiana). (Author/SLD)
Sponsoring Agency: Fund for the Improvement of Postsecondary Education (ED), Washington, DC.
Contract Number: G008730522-89.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Teachers; Curriculum Development; Education Majors; Elementary School Teachers; Elementary Secondary Education; Faculty Development; Higher Education; Interviews; Models; Preservice Teacher Education; Program Implementation; Public School Teachers; Secondary School Teachers; Teacher Certification; Teacher Recruitment; Teacher Supply and Demand; Workshops; Reports, Evaluative